UMP Brisk Walk 3 km Kick-off off Program Gaya Hidup Sihat UMP 2023 - Amy Zulaikha, Mohd Ali (2023)
PEKAN, 10 May 2023 - Universiti Malaysia Pahang (UMP) campuses were buzzing with excitement as Services Management Division (Bahagian Khidmat Pengurusan - BKP) hosted the inaugural UMP Brisk Walk 3 km event.